THE SEMIOTICS ANALYSIS ON INDONESIAN JOURNALISTIC WORKS TIN MINERS TARGET THE OCEAN AS RESERVES DWINDLE ON LAND BY REUTERS - Sahputra, M. Robby; Syaifuddin, Syaifuddin (IJOSMAS, 2023)
Photos have always been the most important element in newspapers. A photo is better able to explain about an event. So that photos cannot be separated from newspapers as a complement to news. Journalistic photos displayed in the mass media, especially in newspapers, are interesting to observe. The popularity of Bangka Belitung tin has become an international concern, Reuters, an international media, reported on the exploitation of tin accompanied by journalistic photographs.The purpose of this study is to analyze how important photojournalism published by Reuters media is for environmental figures in preserving the environment when viewed from a semiotic perspective through the four elements of photojournalism, namely the element of news value (news value), the element of news originality, the element of photo captions, and elements of factual nature, informative, relevant, and using appropriate shooting in the photojournalistic work